Enhanced simultaneous voltammetric detection of dopamine and uric acid using Au@Ni-metal–organic framework-modified electrode - Feng, Zhou; Lim, Hong Ngee; Ibrahim, Izwaharyanie; Endot, Nor Azam; Malek, Emilia Abdul; Gowthaman, N. S. Krishnan (Wiley, 2024)
A novel conductive Ni‐based metal–organic framework (MOF) decorated with Au nanoparticles (AuNPs; Au@Ni‐MOF) was developed and used as a drop‐cast thin‐film electrode to individually and simultaneously quantify dopamine (DA) and uric acid (UA). The Ni‐MOF composite was synthesized using an in situ growth strategy involving the growth of [Ni 3 (BTC) 2 (H 2 O) 6 ]n (BTC = 1,3,5‐benzenetricarboxylate) with coordinatively unsaturated Ni (II) sites. The Ni‐MOF powder was then mixed with a AuNP solution to produce a Au@Ni‐MOF hybrid material. The synthesized Au@Ni‐MOF hybrid material was employed as a surface modifier for a screen‐printed carbon electrode, and its efficacy for the detection of DA and UA was assessed using differential pulse voltammetry (DPV) and cyclic voltammetry. The developed sensor exhibited remarkable sensitivity, achieving low detection limits of approximately 0.027 and 0.028 μM (S/N = 3) in the simultaneous quantification of DA and UA, respectively. The sensor exhibited an extensive linear range of 0.5 μM to 1 mM, coupled with excellent sensitivities for DA and UA of 1.43 and 1.35 μA μM −1 cm −2 , respectively. Furthermore, the sensor performance in human serum and urine samples was successfully validated using DPV, which revealed outstanding recovery rates of 93.8–105.0% with a minimal relative standard deviation below 3%. Moreover, the synthesized Au@Ni‐MOF composite exhibited exceptional dispersion stability, high sensitivity, and remarkable selectivity, which were attributed to the well‐arranged combination of AuNPs and Ni‐MOFs, enabling its use in non‐enzymatic sensing applications targeting DA and UA.